How Does Bribery Affect Public Service Delivery? Micro-Evidence from Service Users and Public Officials in Peru - Kaufmann, Daniel; Montoriol-Garriga, Judit; Recanatini, Francesca (World Bank, Washington, DC, 2012)
When seeking a public service, users may be required to pay in bribes more than the official price. Consequently, some users may be discouraged and choose not to seek a service due to the higher price imposed by the bribery "tax." This paper explores the price and quantity components of the relationship between governance and service delivery using micro-level survey data. The authors construct new measures of governance using data from users of public services from 13 government agencies in Peru. For some basic services, low-income users pay a larger share of their income than wealthier ones do; that is, the bribery tax is regressive. Where there are substitute private providers, low-income users appear to be discouraged more often and not to seek basic services. Thus, bribery may penalize poorer users twice - acting as a regressive tax and discouraging access to basic services. The paper explores the characteristics of households seeking public services. Higher education and age are associated with higher probability of being discouraged. Trust in state institutions decreases the probability of being discouraged, while knowledge of mechanisms to report corruption and extent of social network increase it, suggesting that households may rely on substitutes through networks. The study complements the household analysis with supply-side analysis based on data from public officials, and constructs agency-level measures for access to public services and institutional factors. Econometric results suggest that corruption reduces the supply of services, while voice mechanisms and clarity of the public agency's mission increase it.